141k views
2 votes
F(-2)=-3 and g(-2)=5Find (f+g)(-2)and (f/g)(-2)

User JD Long
by
4.5k points

1 Answer

2 votes

We are given:


\begin{gathered} f(-2)\text{ = -3 and} \\ g(-2)\text{ = 5} \end{gathered}

(a) (f + g)(-2):

Recall that:


(f+g)(x)\text{ = f(x) + g(x)}

Applying this:


\begin{gathered} (f+g)(-2)\text{ = f(-2) + g(-2)} \\ =\text{ -3 + 5} \\ =\text{ 2} \end{gathered}

Hence: (f + g)(-2) = 2

(b) (f/g)(-2):

Recall that:


((f)/(g))(x)\text{ = }(f(x))/(g(x))


\begin{gathered} ((f)/(g))(-2)\text{ = }(f(-2))/(g(-2)) \\ =\text{ }(-3)/(5) \\ =\text{ -}(3)/(5) \end{gathered}

Hence, (f/g)(-2) = -3/5

User Sam Yates
by
4.7k points